Endoscope-Assisted Sutureless Intrascleral Haptic Fixation of a Posterior Chamber Intraocular Lens. (July 2022) - Tandias, Rachel; Lemire, Colin A.; Yu, Gina; Seto, Brendan; Arroyo, Jorge G.
Purpose: In eyes with compromised capsule support, sutureless scleral fixation is a popular method of placing a posterior chamber intraocular lens (PCIOL). We describe an endoscope-assisted sutureless technique for intrascleral fixation of a 3-piece PCIOL. Methods: Eyes of patients who had endoscope-assisted scleral-fixated intraocular lens (SFIOL) implantation were examined retrospectively. The technique comprised direct capture of the IOL haptic with a forceps through a pars plana sclerotomy with subsequent haptic fixation into scleral tunnels created with a 26-gauge needle. The endoscope was used to visualize haptic positioning under the iris and ensure proper centration of the IOL. Results: Thirteen eyes of 13 patients were examined. The mean age of the patients was 68.2 years (range, 38-87 years), and the mean follow-up was 13.6 months (range, 5-23 months). The indications for surgery were a subluxated IOL (6 eyes), postoperative aphakia (5 eyes), and a subluxated cataract (2 eyes). The mean best-corrected visual acuity ± SD improved significantly from 1.2 ± 0.6 logMAR preoperatively to 0.6 ± 0.7 logMAR at last the follow-up (paired Welch t test; t10 = 2.69; P = .023). IOL stability and centration were maintained in all patients. Conclusions: Endoscopic visualization during sutureless SFIOL implantation helped improve haptic localization, minimize intraoperative complications, and achieve excellent IOL centration.